Development of Care Curves Following the Stage 1 Palliation: A Comparison of Intensive Care Among 5 Centers - Francesca Sperotto (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Comparison of care among centers is currently limited to major end points, such as mortality, length of stay, or complication rates. Creating “care curves” and comparing individual elements of care over time may highlight modifiable differences in intensive care among centers. Methods and Results We performed an observational retrospective study at 5 centers in the United States to describe key elements of postoperative care following the stage 1 palliation. A consecutive sample of 502 infants undergoing stage 1 palliation between January 2009 and December 2018 were included. All electronic health record entries relating to mandatory mechanical ventilator rate, opioid administration, and fluid intake/outputs between postoperative days (POD) 0 to 28 were extracted from each institution's data warehouse. During the study period, 502 patients underwent stage 1 palliation among the 5 centers. Patients were weaned to a median mandatory mechanical ventilator rate of 10 breaths/minute by POD 4 at Center 5 but not until POD 7 to 8 at Centers 1 and 2. Opioid administration peaked on POD 2 with extreme variance (median 6.9 versus 1.6 mg/kg per day at Center 3 versus Center 2). Daily fluid balance trends were variable: on POD 3 Center 1 had a median fluid balance of −51 mL/kg per day, ranging between −34 to 19 mL/kg per day among remaining centers. Intercenter differences persist after adjusting for patient and surgical characteristics (P<0.001 for each end point). Conclusions It is possible to detail and compare individual elements of care over time that represent modifiable differences among centers, which persist even after adjusting for patient factors. Care curves may be used to guide collaborative quality improvement initiatives.